2015
DOI: 10.1002/mabi.201500040
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ornithine‐co‐arginine‐co‐glycine‐co‐aspartic Acid): Preparation via NCA Polymerization and its Potential as a Polymeric Tumor‐Penetrating Agent

Abstract: A novel random copolypeptide of ornithine, arginine, glycine, and aspartic acid [Poly(ornithine-co-arginine-co-glycine-co-aspartic acid), Poly(O,R,G,D)] has been prepared through ring-opening polymerization of N-δ-carbobenzoxy-l-ornithine N-carboxyanhydride [Orn(Cbz)-NCA)], l-glycine N-carboxyanhydride (Gly-NCA) and β-benzyl l-aspartate N-carboxyanhydride [Asp(Bn)-NCA], following by subsequent deprotection and guanidization. The structure of Poly(O,R,G,D) was confirmed by nuclear magnetic resonance (NMR) spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Biodegradable polypeptides have potential for medical applications such as carriers for protein conjugates and use in drug delivery systems . Copolypeptides resemble natural proteins in properties such as their degradability by proteolytic enzymes. , However, amino acids in natural proteins are arranged in a well-defined sequence, which leads to characteristic functionalities and properties. Block copolypeptides are interesting for specific applications due to their ability to self-assemble .…”
Section: Introductionmentioning
confidence: 99%
“…Biodegradable polypeptides have potential for medical applications such as carriers for protein conjugates and use in drug delivery systems . Copolypeptides resemble natural proteins in properties such as their degradability by proteolytic enzymes. , However, amino acids in natural proteins are arranged in a well-defined sequence, which leads to characteristic functionalities and properties. Block copolypeptides are interesting for specific applications due to their ability to self-assemble .…”
Section: Introductionmentioning
confidence: 99%
“…They found that due to the multiple chain folding of PGly, the lamellar structure of PBLG was stabilized. Finally, Yu et al [29] used poly(glycine) for synthesizing a polymeric tumor-penetrating agent.…”
Section: Introductionmentioning
confidence: 99%